Optimalisasi Pupuk Organik Cair Berbasis Batang Pisang dan Serabut Kelapa dengan Bioaktivator MA-11 untuk Meningkatkan Pertumbuhan Tanaman - Ida Ayu Putu Suryanti; I Made Pasek Anton Santiasa (Jurnal Penelitian Pendidikan IPA, 2026)
The sustainable utilization of agricultural residues remains challenging because the combined application of banana pseudostem, coconut fiber, and the MA-11 bioactivator for liquid organic fertilizer production has not been systematically investigated. This research aims to analyze the formulation of liquid organic fertilizer from banana pseudostem and coconut fiber, using MA-11 as a bioactivator to enhance plant growth. First part of research focusing on analysing macronutrients, micronutrients, and the total bacterial count (CFU/mL). The best results were liquid organic fertilizer made from varying concentrations (5%, 10%, 15%, 20%, and 25%) as a treatment and a control (0%), each of which was added with 1 L of coconut water, 125 mL of molasses, and 125 mL of MA-11 to be tested on Marigold in the greenhouse. This research uses an experimental method with a Completely Randomized Design. Plant growth responses were assessed by measuring plant height, leaf number, and the dry biomass of roots, stems, and leaves. The research results showed that the combination  3 (K3) with 125 gr of banana stems and 375 gr of coconut fiber had macronutrients (N, P, and K) according to the standard (2-6%), which is 3.38%. The content of micronutrients Cl, Na, Zn, and B was according to standards. The best formulation in this research that can encourage plant growth is K3 with a concentration of 15%. These findings indicate that the success of liquid organic fertilizer is not only determined by the composition of the raw materials but also by the interaction between nutrient content, microorganism activity, and appropriate application concentration.